1987
DOI: 10.1021/bi00381a032
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline antibiotics. Interaction with DNA and nucleosomes and inhibition of DNA synthesis

Abstract: We report studies of the interaction of four anthracycline antibiotics, iremycin (IM), daunomycin (DM), aclacinomycin A (AM), and violamycin B1 (VM), with naked DNA, nucleosomal core particles, and 175 base pair (bp) nucleosomes lacking histone H1. In all cases the binding strength increases in the order IM less than DM approximately AM less than VM. The binding substrates increased in affinity for the drugs in the following order: core particles less than 175-bp nucleosomes less than DNA. The apparent DNA len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…Consistent with our data, however, their studies have also shown that binding of daunomycin to 175 bp (histone H1-depleted) of nucleosomes is strongly reduced relative to its affinity for free DNA (14). Their findings also agree with our results that the affinity of daunomycin for different nucleohistone complexes increases in the following order: nucleosome core particle Ͻ 175 bp nucleosome Ͻ DNA (38). Thus it appears as if the affinity of the drug for the chromatin complexes decreases with the decrease of the number of base pairs in the DNA region flanking the DNA coils protected by the histone octamer.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our data, however, their studies have also shown that binding of daunomycin to 175 bp (histone H1-depleted) of nucleosomes is strongly reduced relative to its affinity for free DNA (14). Their findings also agree with our results that the affinity of daunomycin for different nucleohistone complexes increases in the following order: nucleosome core particle Ͻ 175 bp nucleosome Ͻ DNA (38). Thus it appears as if the affinity of the drug for the chromatin complexes decreases with the decrease of the number of base pairs in the DNA region flanking the DNA coils protected by the histone octamer.…”
Section: Discussionsupporting
confidence: 91%
“…(37)(38)(39)(40) It was shown that the affinity of daunomycin for different nucleohistone complexes is in the following order: DNA > 175 bp H1/H5 depleted nucleosomes > nucleosome core particles. (14,38) These results are in agreement with those observed for the interaction of daunomycin with chromatin containing either the full native linker histones (H1 and H5) or depleted of these histones. (21) Addition of daunomycin to 175 bp H1-depleted nucleosomes or 146 bp nucleosome core particles stabilizes their low melting transition temperature, which corresponds to the regions of the nucleosomal DNA less tightly bound to the histone octamer at the flanking ends of the particle.…”
Section: Introductionsupporting
confidence: 87%
“…(10,11) Although there is still some controversy about their mode of action, the anticancer activity or cytotoxic effects may involve the interaction with nuclear components, especially DNA and type II topoisomerases; they may also participate in the inhibition of DNA and RNA synthesis. (9,(12)(13)(14) Characterization of the binding sites of antitumor drugs in the cell is important because it can provide clues required for further drug design to enhance drug efficacy. This review focuses its attention on progress made on the understanding of the interaction of anthracycline antibiotics adriamycin and daunomycin with different chromatin components.…”
Section: Introductionmentioning
confidence: 99%
“…When used clinically, it is likely that daunomycin and adriamycin act on DNA in the form of its chromatin complex [16]. For this reason a study of the effects of free lysine and arginine on 2FD binding preference between d(G-C)s and d(A-T)s was undertaken, the aim having been to establish whether anthracycline binding site selectivity might be affected by DNA-histone association.…”
Section: Effects Of Lysine and Argininementioning
confidence: 99%